Open for All: How Are Federal and Municipal Land Management Agencies Adapting to the COVID-19 Pandemic Alongside Increased Societal Recognition of Racial Injustice - Svendsen, Erika S.; Campbell, Lindsay K.; Plitt, Sophie; Johnson, Michelle L. (Frontiers in Sustainable Cities, 2021)
In addition to impacts on human health and the economy, COVID-19 is changing the way humans interact with open space. Across urban to rural settings, public lands–including forests and parks – experienced increases and shifts in recreational use. At the same time, certain public lands have become protest spaces as part of the public uprisings around racial injustice throughout the country. Land managers are adapting in real-time to compound disturbances. In this study, we explore the role of the public land manager during this time across municipal and federal lands and an urban-rural gradient. We ask: How adaptable are public land managers and agencies in their recreation management, collaborative partnerships, and public engagement to social disturbances such as COVID-19 and the co-occurring crisis of systemic racial injustice brought to light by the BLM uprisings and protests? This paper applies qualitative data drawn from a sample of land managers across the northeastern United States. We explore management in terms of partnership arrangements, recreational and educational programs, and stakeholder engagement practices and refine an existing model of organizational resilience. The study finds abiding: reports of increased public lands usership; calls for investment in maintenance; and need for diversity, equity, and inclusion in both organizational settings and landscapes themselves; and the need for workforce capacity. We discover effective ways to respond to compound disturbances that include open and reflective communication, transforming organizational cultures, and transboundary partnerships that are valued as critical assets.